The effects of an eight week grouped exercise programme on gross motor proficiency in children with minimal motor dysfunction. - Kolesky, Jacqueline Mary (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScPhysio)--Stellenbosch University, 2017.